CONCEPTS FOR THE DEVELOPMENT OF THE GERMAN MODEL OF ADMINISTRATIVE PROCEDURE - Markova, Olena (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article examines the doctrinal concepts of the development of the German model of administrative procedure. Research methods: the chosen topic of scientific research requires the use of various scientific methods and approaches to obtain analysis such as historical, systematic methods. Discussion: the analysis and research of the concepts of Otto Meyer on the administrative act, Walter Jelinek on subjective public law, and Max Weber on rational bureaucracy made it possible to assess the influence of their concepts on the development and formation of the German model of administrative procedure. The concept of an administrative act was taken as the basis for the future Federal Law on Administrative Procedure, in which the provisions on the administrative act received a detailed justification and consolidation. The concept of subjective public rights was very important for the administrative procedure in the matter of challenging an administrative act. Results: the above-mentioned concepts laid the foundations for the normative model of administrative procedure, which found its legitimate consolidation in the Law of the Federal Republic of Germany "On Administrative Procedure".